Positive Impact of the Local Wisdom Module on the Canang Kayu Musical Instrument: Building the Character of Love for the Homeland - Erna Wati; Josephat Kigo; Kullawat Inthaud (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The aim of this research is to determine the effect of using local wisdom-based modules on students' character of love for their homeland. Methodology: This research adopts a quantitative methodological approach with a quasi-experimental type. This research uses junior high school students who study vibrations, waves and sound as research samples. This study applied two main data collection techniques, namely a love of the country character questionnaire and a response questionnaire. student. Meanwhile, the data analysis technique used in this research is by conducting assumption tests and simple linear regression tests. Main Findings: Based on the results of the data analysis carried out, it was found that there was an influence of the use of local wisdom modules on the character of love for the country, namely an RSquare value of 0.616, which means that 61.6% of the local wisdom modules had an effect on the character of love for the country. There is an influence of the local wisdom module on the character of patriotism, this can be seen from the significance value < 0.05. The significance value obtained is 0.009. Novelty/Originality of this study: The novelty of this research lies in a holistic approach that combines elements of music, culture and the environment in order to build students' character of love for their homeland through a physics learning module based on local wisdom of the Canang Kayu musical instrument. The findings of this research are a physics teaching strategy that is oriented towards ethnophysics.